Method for manufacturing fiber material with thermoplastic polymer pre-impregnated in fluid bed

JP2025041649APending Publication Date: 2025-03-26ARKEMA FRANCE SA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024209206
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-12-18
Filing Date
2024-12-02
Publication Date
2025-03-26

Smart Images

  • Figure 2025041649000001_ABST
    Figure 2025041649000001_ABST
Patent Text Reader

Abstract

To provide a fiber material including a continuous fiber and a method for manufacturing a material including a thermoplastic polymer matrix.SOLUTION: In a method, a material is formed as a unidirectional band, a step of pre-impregnation of a strand 81a of a fiber material with a matrix in a powder form is included, the pre-impregnation step is run in a fluid bed 22 including a grooved roller component 82, the strand 81a is in contact with a surface of the roller component 82 and includes a siding of 0.1 wt.% or under, and a speed of the matrix, when introduced to the fluid bed, is controlled by always controlling a tension of the strand 81a by controlling a retention time in the powder.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a fibrous material pre-impregnated with a thermoplastic polymer in a fluidized bed.

[0002] More particularly, the invention relates to a method for producing a pre-impregnated fibrous material, comprising a step of pre-impregnation of the fibrous material with no or little sizing, in order to produce an impregnated fibrous material with reduced and controlled porosity, in particular up to the core, and to obtain bands of impregnated fibrous material with calibrated dimensions that can be directly used to produce three-dimensional composite parts. [Background technology]

[0003] In this document, "fibrous material" refers to an assembly of reinforcing fibres. Before being pre-impregnated and moulded, it has the form of a strand. After moulding, and in particular impregnation up to the core of the fibre strand, it has the form of a band (or tape), a strip or a layer. If the reinforcing fibres are continuous, the assembly constitutes a fabric or a non-woven fabric (NCF). If the fibres are short, the assembly constitutes a felt or a fibre mat.

[0004] In this specification the term "strip" is used to refer to a narrow piece of fibrous material having a width of 400mm or more, and the term "band" is used to refer to a band having a calibrated width of 400mm or less.

[0005] The term "strand" is used to refer to fibrous material.

[0006] Such pre-impregnated fiber materials are particularly suitable for producing light composite materials for the manufacture of mechanical parts with three-dimensional structure and good mechanical and thermal properties. If the fibers are composed of carbon or the resin is filled with suitable additives, these fiber materials are able to discharge static charges. Thus, they have properties that are particularly compatible with the manufacture of parts in the fields of machinery, civil or military aviation, maritime, automotive, oil and gas, especially marine, gas storage, energy, health care, weapons and armaments, sports and recreation, and electronics.

[0007] However, the use of unsized fibers is necessary for aeronautical and marine applications. Indeed, especially for manufacturing structural parts and / or parts exposed to extreme chemical / thermal environments, the polymers used not only need to be able to withstand the stresses of the part, but also the fiber / matrix interface needs to have the best potential for better strength of the composite, both in terms of mechanical stress transmission from the resin to the fiber and chemical resistance. The strength of these connections between the matrix and the fibers is dictated by the impregnation quality (limited porosity) of the material and by the nature of the physicochemical or homogeneous mechanical connections between the fiber and the polymer matrix.

[0008] With the aim of improving the physicochemical link between the polymer and the fiber, fiber manufacturers use sizings, the composition and the level of which can vary. Currently, generally organic in nature (thermosetting or thermoplastic resin type) and very frequently formulated for impregnation of fibers with polymers having a low melting point or with thermosetting polymers having a low Tg point, the sizing is often degraded by the impregnation method, especially during the pre-impregnation step (melting process, passage through a solvent solution, etc.) and / or during the melting step of the thermoplastic matrix, especially if it has a high melting point (for semi-crystalline) or a high Tg (for amorphous or thermosetting). Moreover, the chemical compatibility between the polymer of the matrix and the sizing is not always optimal; the resulting bond strength may be modified, either positively or negatively, compared to that observed with the unsized fiber.

[0009] This therefore gives rise to a number of difficulties for the manufacture of tapes using the method of pre-impregnation with dry powders (or a mixture of dry powders), especially in the case where each strand is pre-impregnated with the powder separately from the others. In most cases, the strands are guided by a roller component (generally in the form of a roller) placed in a bath containing either a fluidized bed or an aqueous dispersion.

[0010] Thus, international application WO2018115736 describes a method for pre-impregnating a fibrous material in a fluidized bed, in which the powder content depends on the residence time in the fluidized bed and the tension of the strands is controlled using a creel present in front of the tank containing the fluidized bed.

[0011] The use of at least one roller component in the fluidized bed (in particular a cylindrical roller of concave, convex or cylindrical shape) makes it possible to improve the pre-impregnation with respect to the prior art methods, the fibrous material used may be sized or unsized.

[0012] It is not at all specified in this application whether the rollers used are smooth or grooved (or notched).

[0013] An article by Gibson A. et al. (composites manufacturing, Vol. 3, No. 4 (1992)) describes a process of pre-impregnation in a fluidized bed of fibrous material with a thermoplastic polymer, including a smooth roller in the fluidized bed with control of the fiber content, using a vibration system placed at the bath outlet.

[0014] However, when these rollers are smooth, the fact that the fibers are not sized causes a very significant and especially a very variable expansion of the fiber strands, which directly affects the powder level carried by the fiber strands, making this level variable and uncontrollable.

[0015] Under low tension conditions, whether the fibers are sized or not, residence time control is no longer sufficient to control the powder level, and too low tension causes twisting and / or bending of the strands.

[0016] However, in the case of unsized fibers, excessive tension in the fibers can cause damage to the latter in contact with the rollers, generate significant fuzz, contaminate the fluidized bed and upset the quality of the fluidization and therefore of the pre-impregnation of the tape.

[0017] It is therefore necessary to be able to continuously control the dust level with unsized fibres over time without damaging them. Summary of the Invention

[0018] The present invention therefore aims to address the shortcomings of the prior art.

[0019] The present invention therefore relates to a method for producing a pre-impregnated fibrous material comprising continuous fibres and at least one thermoplastic polymer matrix, comprising a step of pre-impregnating, particularly uniformly, said fibrous material in the form of a strand or several parallel strands with at least one thermoplastic polymer matrix in powder form, said pre-impregnation step being carried out on unsized fibrous material in a vessel comprising a fluidised bed equipped with grooved cylindrical rollers.

[0020] The invention also relates to a unidirectional band of impregnated fibre material, in particular a band wound on a spool, characterized in that it is obtained using the method defined above.

[0021] The invention further relates to the use of a band as defined above in the manufacture of a three-dimensional part. Said manufacture of said composite parts relates to the fields of transportation, in particular automotive, oil and gas, in particular marine, gas storage, civil or military aviation, offshore, railway; renewable energy, in particular wind energy, tidal energy, energy storage devices, solar panels; thermal protection panels; sports and recreation, health and medicine, security and electronics.

[0022] The invention also relates to a three-dimensional composite part, characterised in that it results from the use of at least one unidirectional band of impregnated fibre material as defined above. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The invention relates to a method for producing a pre-impregnated fibrous material made of continuous fibers and comprising at least one thermoplastic polymer matrix, said pre-impregnated fibrous matrix being produced as a single unidirectional band or a number of unidirectional parallel bands, said method comprising a step of pre-impregnating, in a particularly homogeneous manner, said fibrous material still in the form of a strand (81a) or several parallel strands, with said at least one thermoplastic polymer matrix in powder form, said pre-impregnation step being carried out by a dry process in a vessel (20) comprising a fluidized bed (22) comprising at least one grooved roller component (82),

[0024] the strands (81 a) contact a portion or all of a surface of the at least one grooved roller component (82), the strands (81 a) comprising 0.1% by weight or less of a sizing;

[0025] The control of the proportion of the at least one thermoplastic polymer matrix in the fibrous material is characterized in that it is achieved by controlling the residence time of the fibrous material in the powder as the strands (81a) pass through the fluidized bed and by constant control of the tension of the strands (81a).

[0026] Advantageously, the method according to the invention excludes any electrostatic methods using deliberate charges.

[0027] The term "sizing" refers to a surface treatment applied to fibrous materials during manufacture. It may also refer to a fusible pretreatment at the beginning of a pre-impregnation step, whether or not performed in direct conjunction with impregnation. It may also refer to a fusible pretreatment at the beginning of a pre-impregnation step, whether or not performed in direct conjunction with impregnation.

[0028] They are generally organic in nature (thermosetting or thermoplastic resin type) and are very frequently formulated for pre-impregnation of the reinforcing fibers with a polymer having a low melting point Tm or a thermosetting polymer having a low Tg point.

[0029] These sizings also help protect the dry fibers from damage during contact with the guide system.

[0030] Said fibre material may thus contain up to 0.1% by weight of organic material called sizing (thermosetting or thermoplastic resin type).

[0031] In the case of a volatile pretreatment carried out by an impregnation device, for example at the beginning of a process for pre-impregnating the reinforcing fibers, the sizing may be an organic liquid such as water, low or high molecular weight alcohols (e.g., ethanol, methanol, isopropanol), ketones (acetone, etc.), etc., which serves as a volatile sizing; i.e., it is present for a short period in contact with the fibers, allowing them to be handled in a "dry" state (i.e., prior to pre-impregnation), and then it is removed from the composite so as not to perturb the final properties of the composite.

[0032] Advantageously, said strands (81a) are not sized, especially in the case of amorphous thermoplastic resins with a high Tg or semi-crystalline resins with a high melting point, in which case the sizing would deteriorate when exposed to the high temperatures of the conversion process imposed by the nature of these resins.

[0033] This means that said strands (81a) are either substantially devoid of sizing due to the fact that the fibrous material has previously been desized, or are devoid of sizing because the original fibrous material was not sized.

[0034] For desizing, several solutions exist: - Heating in a humid environment, generally because the sizing is deposited in a solution containing an aqueous base during the manufacture of the fiber. Otherwise pre-impregnation methods, generally because it is a treatment before spooling: - Thermal degradation It is necessary to arrange it in accordance with the introduction of the sizing into the solvent (water or another organic solvent).

[0035] Advantageously, the particles of the thermoplastic polymer powder have a mean volume diameter D50 of between 30 and 300 μm, in particular between 50 and 200 μm and more particularly between 70 and 200 μm.

[0036] The expression "residence time in powder" means the time that the strand is in contact with said powder in the fluidized bed.

[0037] The inventors have found by chance that when unsized fibrous material is used for a pre-impregnation step in a fluidized bed, control of the residence time in the powder is no longer sufficient to homogeneously pre-impregnate the fibrous material into the thermoplastic polymer matrix, especially with a well-controlled powder (resin) level, and that the pre-impregnation step requires the presence of one or several grooved rollers in the fluidized bed with simultaneous control of the tension of said fibrous material at the inlet of the fluidized bed.

[0038] There is a critical tension called Tc that leads to fiber damage (fuzzing), above which Tc' impregnation becomes impossible because the tension blocks the expansion of the strands in the fluidized bed. In general, for unsized fibers, Tc <Tc’である。

[0039] There is also Tmin, the tension below which twisting appears.

[0040] Advantageously, the tension T in said strand (81a) is less than Tc when it penetrates the fluidized bed.

[0041] Advantageously, the tension T in said strand (81a) is greater than Tmin when it penetrates the fluidized bed.

[0042] Advantageously, the tension T in said strand (81a) when it penetrates the fluidized bed is less than Tc and greater than Tmin.

[0043] Throughout this specification the fibrous material after passing through the fluidized bed is referred to as pre-impregnated fibrous material and after heating and / or calendering is referred to as impregnated fibrous material.

[0044] The fibre content and porosity measurements are carried out on the impregnated fibre material, therefore after heating and / or calendering.

[0045] The term "homogeneous" means that the pre-impregnation is uniform and there are no dry fibers at the surface of the pre-impregnated fibrous material.

[0046] Polymer Matrix

[0047] Thermoplastic or thermoplastic polymer generally refers to a material that is solid at room temperature, may be semi-crystalline or amorphous, and if it is amorphous, will soften during temperature increase, especially after passing its glass transition temperature (Tg), and flow at higher temperatures, or if it is semi-crystalline, may exhibit a sharp transition once it has passed its so-called melting temperature (Tm), and when the temperature is reduced, will become solid once again below its crystallization temperature (for semi-crystalline) and its glass transition temperature (for amorphous).

[0048] Tg and Tm are determined by differential scanning calorimetry (DSC) according to standards 11357-2:2013 and 11357-3:2013, respectively.

[0049] As regards the polymer constituting the pre-impregnated matrix of the fibrous material, it is advantageously a thermoplastic polymer or a mixture of thermoplastic polymers, which is milled in powder form so that it can be used in an apparatus such as a bath, in particular in a fluidized bed.

[0050] The vessel configuration, especially the fluidized bed apparatus, can be open or closed.

[0051] Optionally, the thermoplastic polymer or blend of thermoplastic polymers further comprises a carbon-based filler, in particular carbon black or a carbon-based nanofiller, preferably selected from carbon nanofillers, in particular graphene and / or carbon nanotubes and / or carbon nanofibrils or blends thereof, which make it possible to conduct electricity and heat, thus improving the lubrication of the polymer matrix when heated.

[0052] Optionally, said thermoplastic polymer comprises at least one additive selected in particular from catalysts, antioxidants, heat stabilizers, UV stabilizers, light stabilizers, lubricants, fillers, plasticizers, flame retardants, nucleating agents, chain extenders and dyes, or mixtures thereof.

[0053] According to another variant, the thermoplastic polymer or mixture of thermoplastic polymers can further comprise a liquid crystal polymer or a cyclized polybutylene terephthalate, or a mixture containing the latter, such as the CBT100 resin marketed by CYCLICS CORPORATION. These compounds make it possible, in particular, to make the polymer matrix flowable in the molten state for better penetration to the core of the fibers. Depending on the nature of the polymer or mixture of thermoplastic polymers used to create the pre-impregnated matrix, in particular its melting temperature, one or the other of these compounds is selected.

[0054] The thermoplastic polymers included in the composition of the pre-impregnated matrix of the fibrous material are:

[0055] - polymers and copolymers from the group of aliphatic, cycloaliphatic or semi-aromatic polyamides (PA), also called polyphthalamides (PPA), - polyureas, in particular aromatic polyureas; - the polymers and copolymers of the acrylic group, such as the polyacrylates, more particularly polymethyl methacrylate (PMMA) or its derivatives; - polymers and copolymers from the group of polyaryletherketones (PAEK), such as polyetheretherketones (PEEK), or poly(aryletherketoneketones) (PAEKK), such as poly(etherketoneketones) (PEKK) or their derivatives; - aromatic polyether-imide (PEI), - polyarylsulfides, in particular polyphenylsulfide (PPS), - polyarylsulfides, in particular polyphenylene sulfone (PPSU), - polyolefins, in particular polypropylene (PP), - Polylactic acid (PLA), - Polyvinyl alcohol (PVA), It may be chosen from fluorinated polymers, in particular polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE) or polychlorotrifluoroethylene (PCTFE), and mixtures thereof.

[0056] Advantageously, when said thermoplastic polymer is in the mixture, it is added to the tank either in powder form previously obtained by dry blending or by grinding compound, or directly in the form of an in situ dry blend.

[0057] Advantageously, it is added to the bath either in the form of a powder previously obtained by dry blending, or directly in the form of an in situ dry blend, the mixture being a mixture of PEKK and PEI.

[0058] Advantageously, when said polymer is a mixture of two polymers P1 and P2, the weight proportion of polymers P1 and P2 is from 1-99% to 99-1%.

[0059] Advantageously, the PEKK / PEI mixture is between 90-10% and 60-40% by weight, in particular between 90-10% and 70-30% by weight.

[0060] The thermoplastic polymer may correspond to a final non-reactive polymer with which the fibrous material is impregnated, or to a reactive prepolymer which also impregnates the fibrous material but which, after pre-impregnation, may react with itself or with another prepolymer or with a chain extender, depending on the chain ends which said prepolymer carries, in particular during heating on a roller in an oven and / or during mounting of the tape in the final method for producing the composite part.

[0061] According to a first possibility, said prepolymer may comprise or consist of at least one carrier-reactive prepolymer (polyamide) on the same chain (i.e. on the same prepolymer), which has two terminal functional groups X' and Y', which are functional groups that are co-reactive with each other by condensation, more specifically X' and Y' are amine and carboxy or carboxy and amine, respectively. According to a second possibility, said prepolymer may comprise or consist of at least two polyamide prepolymers, which are reactive with each other, each carrying two identical terminal functional groups X' or Y', respectively (same for the same prepolymer and different between the two prepolymers), said functional group X' of a prepolymer can react only with said functional group Y' of the other prepolymer, in particular by condensation, more specifically X' and Y' are amine and carboxy or carboxy and amine, respectively.

[0062] According to a third possibility, said prepolymer may comprise or consist of at least one prepolymer of said thermoplastic polyamide polymer, carrying n terminal reactive functional groups X chosen from -NH2, -CO2H and -OH, preferably NH2 and -CO2H, n being 1 to 3, preferably 1 to 2, more preferably 1 or 2 and more particularly 2, and carrying at least one chain extender Y-A'-Y, where A' is a non-polymeric hydrocarbon divalent substituent, which has two identical terminal reactive functional groups Y and is reactive by polyaddition with at least one functional group X of said prepolymer a1), and preferably has a molecular weight of less than 500, more preferably less than 400.

[0063] The number average molecular weight Mn of said final polymer of the thermoplastic matrix is ​​preferably in the range from 10 000 to 40 000, preferably from 12 000 to 30 000. These Mn values ​​may correspond to an intrinsic viscosity of 0.8 or more, determined in m-cresol according to standard ISO 307:2007, but with a different solvent (m-cresol instead of sulfuric acid, temperature 20° C.).

[0064] Said reactive prepolymers according to the two options listed above have a number average molecular weight Mn ranging from 500 to 10,000, preferably from 500 to 6,000, in particular from 2,500 to 6,000.

[0065] The Mn is determined by calculation from the proportion of terminal functional groups, determined in particular by potentiometric titration in solution, and the functionality of the prepolymer. The mass Mn can also be determined by steric exclusion chromatography or NMR.

[0066] The nomenclature used to define polyamides is described in ISO standard 1874-1:2011 "Plastiques -- Materiaux polyamides (PA) pour moulage and extrusion -- Partie 1: Designation", in particular page 3 (Tables 1 and 2), and is well known to the skilled person.

[0067] The polyamide can be a homopolyamide or a copolyamide or a mixture thereof.

[0068] Advantageously, the polymer constituting the matrix is ​​chosen from polyamides (PA), in particular aliphatic polyamides, in particular PA11 and PA12, cycloaliphatic polyamides, and semi-aromatic polyamides (polyphthalamides), optionally modified with urea groups, and their copolymers, polymethyl methacrylate (PPMA) and their copolymers, polyetherimides (PEI), and fluorinated polymers such as poly(phenylene sulfide) (PPS), poly(phenylene sulfone) (PPSU), polyether ketone ketone (PEKK), polyether ether ketone (PEEK), and poly(vinylidene fluoride (PVDF).

[0069] For fluorinated polymers, vinylidene fluoride (VDF, formula CH 2 =CF 2 It is possible to use homopolymers of VDF, or copolymers of VDF, which contain, by weight, at least 50% VDF and at least one other monomer copolymerizable with VDF. The VDF level must be more than 80% by weight, or better still more than 90% by weight, in order to provide good mechanical strength of the structural parts, especially when subjected to thermal and chemical stress. The comonomer must be a fluorinated monomer, e.g. vinyl fluoride.

[0070] For structural parts which have to withstand high temperatures, apart from fluorinated polymers, PAEKs (polyaryletherketones) are advantageously used according to the invention, such as poly(etherketone) PEK, poly(etheretherketone) PEEK, poly(etherketoneketone) PEKK, poly(etherketoneetherketoneketone) PEKEKK or PAs with high glass transition temperatures Tg.

[0071] Advantageously, said thermoplastic polymer is one having a glass transition temperature Tg≧80° C., or a semi-crystalline polymer having a melting temperature Tm≧150° C.

[0072] Advantageously, said thermoplastic polymer is an aliphatic polyamide chosen from polyamide 6 (PA-6), polyamide 11 (PA-11), polyamide 12 (PA-12), polyamide 66 (PA-66), polyamide 46 (PA-46), polyamide 610 (PA-610), polyamide 612 (PA-612), polyamide 1010 (PA-1010), polyamide 1012 (PA-1012) or mixtures thereof, or a copolyamide thereof, semi-aromatic polyamides, optionally modified with urea units, in particular semi-aromatic polyamides of formula X / YAr as described in EP 1505099, in particular semi-aromatic polyamides of formula A / XT, in which A is selected from units resulting from amino acids, units resulting from lactams and units corresponding to formula (Ca diamine, Cb diacid), where a represents the number of carbon atoms of the diamine and b represents the number of carbon atoms of the diacid, a and b each being between 4 and 36, advantageously between 9 and 18, the units (Ca diamine) being selected from linear or branched aliphatic diamines, cycloaliphatic diamines and alkylaromatic diamines and the units (Cb diacid) being selected from linear or branched aliphatic diacids, cycloaliphatic diacids and aromatic diacids; XT denotes units obtained by polycondensation of Cx diamines with terephthalic acid, x representing the number of carbon atoms of the Cx diamine, x being between 6 and 36, advantageously between 9 and 18, in particular polyamides of the formula A / 6T, A / 9T, A / 10T or A / 11T, where A is as defined above, in particular polyamides PA6 / 6T, PA66 / 6T, PA6I / 6T, PA MPMDT / 6T, PA MXDT / 6T, PA PA11 / 10T, PA11 / 6T / 10T, PA MXDT / 10T, PA MPMDT / 10T, PA BACT / 10T, PA BACT / 6T, PA BACT / 10T / 6T PA 11 / BACT / 10T, PA 11 / BACT / 6T, PA 11 / MPMDT / 10T and PA 11 / MXDT / 10T, and block copolymers, especially polyamide / polyether (PEBA).

[0073] T corresponds to terephthalic acid, MXD corresponds to m-xylylenediamine, MPMD corresponds to methylpentamethylenediamine, and BAC corresponds to bis(aminomethyl)cyclohexane.

[0074] Fiber Material:

[0075] As regards the fibres which constitute said fibre material, these are in particular mineral, organic or vegetable fibres.

[0076] As already mentioned previously in this specification, said fibre material may therefore contain up to 0.1% by weight of organic material called sizing (thermosetting or thermoplastic resin type).

[0077] Advantageously, said strands (81a) are unsized.

[0078] This means that said strands (81a) are either substantially devoid of sizing due to the fact that the fibrous material has previously been desized, or are devoid of sizing because the original fibrous material was not sized.

[0079] The mineral fibres are, for example, carbon fibres, glass fibres, basalt fibres, silica fibres or silicon carbide fibres. The organic fibres are, for example, fibres based on thermoplastic or thermosetting polymers, such as semi-aromatic polyamide fibres, aramid fibres or polyolefin fibres, preferably based on an amorphous thermoplastic polymer and having a glass transition temperature Tg higher than the Tg of the polymer or thermoplastic polymer mixture constituting the pre-impregnated matrix when it is amorphous, or higher than the Tm of the polymer or thermoplastic polymer matrix constituting the pre-impregnated matrix when it is semi-crystalline. Advantageously, they are based on a semi-crystalline thermoplastic polymer and have a melting temperature Tm higher than the Tg of the polymer or thermoplastic polymer mixture constituting the pre-impregnated matrix when it is amorphous, or higher than the Tm of the polymer or thermoplastic polymer matrix mixture constituting the pre-impregnated matrix when it is semi-crystalline. Thus, there is no risk of the organic fibres constituting the fibre material melting during the impregnation of the final composite with the thermoplastic matrix. Plant fibers include natural linen, hemp, lignin, bamboo, silk, especially spider silk, sisal, and other cellulosic fibers, especially viscose. These plant fibers can be used pure or can be treated or coated with a coating layer to facilitate adhesion and impregnation of the thermoplastic polymer matrix.

[0080] The textile material can also be a fabric, braid, or woven with fibers.

[0081] It can also accommodate fibers having supporting threads.

[0082] These component fibers can be used alone or in a mixture. Thus, organic fibers can be mixed with mineral fibers that are pre-impregnated with a thermoplastic polymer powder to form a pre-impregnated fibrous material.

[0083] The organic fiber strands can have several basis weights and can have several geometries. The fibers can be in the form of staple fibers, which then compose felts or nonwovens, which can be in the form of strips, layers, or pieces, or in the form of continuous fibers that compose unidirectional (UD) or 2D fabrics, braids, or strands of nonwoven fibers. The component fibers of the fiber material can further be in the form of a mixture of these reinforcing fibers with different geometries. Preferably, the fibers are continuous.

[0084] Preferably, the fibrous material consists of continuous carbon, glass or silicon carbide fibres or mixtures thereof, in particular carbon fibres, used in the form of a strand or several strands.

[0085] Impregnated materials are also called "ready to use" and are obtained from pre-impregnated fibrous materials after melting of the powder or powder mixture. In this type of impregnated material, the polymer or mixture of thermoplastic impregnating polymers is dispensed to obtain a minimum porosity, i.e. a minimum of empty spaces between the fibers. In fact, the presence of pores in this type of material can act as stress concentration points, for example during mechanical tensile stress loading, which then form crack initiation points of the impregnated fibrous material and mechanically damage it. The reduced porosity therefore improves the mechanical strength and homogeneity of the composite materials formed from these pre-impregnated fibrous materials.

[0086] Therefore, for a "ready to use" impregnated material, the fibre level in said impregnated fibrous material is between 45 and 65% by volume, preferably between 50 and 60% by volume, especially between 54 and 60% by volume.

[0087] The level of impregnation can be measured by image analysis (especially with a microscope or a camera or digital camera) of the cross-section of the band, dividing the surface area of ​​the band impregnated with the polymer by the total surface area of ​​the product (impregnated surface area plus pore surface area). In order to obtain good quality images, the transversely cut band is preferably coated with a standard polishing resin and polished according to standard protocols to allow observation of the sample under a microscope at a magnification of at least 6x.

[0088] Advantageously, the porosity level of said impregnated fibrous material after melting of the powder present in the pre-impregnated strand and impregnation up to the core of the fibres is between 0% and 30%, in particular between 1% and 10%, in particular between 1% and 5%.

[0089] The porosity level corresponds to the closed porosity level and can be determined by electron microscopy or as the relative deviation between the theoretical and experimental density of said pre-impregnated fibrous material as described in the Examples section of the present invention.

[0090] Pre-impregnation process:

[0091] An example of an installation for carrying out the production method is described in International Application WO2015 / 121583 and shown in FIG. 1, but excluding the vessel (otherwise called a pre-impregnation vessel, which contains a fluidized bed with a grooved roller component (FIG. 3), which in the present case may be a grooved cylindrical roller (FIG. 4)).

[0092] In Figures 1-9, the roller components or rollers are perpendicular to the fluidized bed and the grooves are not visible, which are only visible in the front view (Figures 2 and 4).

[0093] All of the cylindrical rollers shown in Figures 1-9 are grooved.

[0094] The grooves can be of any shape and, if the roller is smooth and cylindrical, will have a width less than that which a strand having a diameter equal to the diameter at the bottom of the groove would have under the same conditions of fluidization of the powder and tension of the strand.

[0095] The cylindrical rollers may be fixed or controlled in rotation (ie not free).

[0096] There may be several rollers and, if the rotation is controlled, they may be co-rotating or counter-rotating.

[0097] The pre-impregnation step of the fibrous material is carried out by passing one or more strands through a continuous pre-impregnation apparatus, which comprises a vessel (20) containing a fluidized bed (22) of polymer powder.

[0098] The polymer powder is suspended in a gas G (eg air) introduced into the vessel and circulates within the vessel through a hopper 21. The strands circulate within this fluidized bed 22.

[0099] The vessel may have any shape, in particular a cylinder or parallelepiped, in particular a rectangular prism or cube, preferably a rectangular prism.

[0100] The vessel can be of the open or closed type, preferably of the open type.

[0101] If the vessel is of the closed type, it is equipped with a sealing system so that the polymer powder cannot leave said vessel.

[0102] This pre-impregnation step is therefore carried out in a dry process, ie the thermoplastic polymer matrix is ​​in powder form and is in particular capable of being suspended in a gas, in particular air, but not dispersible in a solvent or in water.

[0103] Each strand to be pre-impregnated is unwound from the device (10) on a reel (11) under the traction force created by a cylinder (not shown). Preferably, the device (10) comprises several reels (11), each reel making it possible to unwind a strand to be impregnated. It is therefore possible to pre-impregnate several textile strands simultaneously. Each reel (11) is equipped with a brake (not shown) to tension each textile strand. In this case, an adjustment module (12) makes it possible to arrange the textile strands parallel to one another. In this way, the textile strands cannot come into contact with one another, which makes it possible to avoid mechanical damage of the fibers due to friction against one another.

[0104] The strand of fibers or parallel strands of fibers then enter a vessel (20) containing a fluidized bed (22) equipped with a grooved roller component, which in the case of Figure 1 in particular is a cylindrical roller with several grooves (one per strand) (23). The strand of fibers or parallel strands of fibers then exit the vessel after impregnation controlled by constant control of the residence time in the powder and the tension of said strands (81a) as they pass through the fluidized bed.

[0105] Advantageously, the tension in said strand (81a) when passing through the fluidized bed is at most 1000 g.

[0106] The tension in the strands can be measured either manually at several points on the line intermittently using a tension meter, or using strain gauges built into elements that contact the strands.

[0107] Advantageously, the tension of said strand (81a) when passing through the fluidized bed is between 100 and 1000 g, in particular between 200 and 1000 g, more particularly between 300 and 850 g.

[0108] In one embodiment, the pre-impregnation step is carried out with simultaneous expansion of the strands (81a) between the inlet and the outlet of the fluidized bed (22).

[0109] Advantageously, the minimum width of said strands (81a) is greater than the width of the groove of said grooved roller component.

[0110] The tension applied to the fiber strand must be sufficient so that the entire groove is always filled with fiber strand, with the minimum width of the free strand being greater than the width of the groove. The minimum width of the strand refers to the width that the strand would have on a smooth roller with the same diameter as that of the groove bottom under the same tension and powder fluidization conditions. This width can advantageously be measured by different methods even on a roller completely submerged in the powder, for example using a pressure sensor, on a smooth roller using a position sensor (LVDT type), then transferred to the use of a grooved roller, the groove width is smaller than the minimum value read using the sensor.

[0111] The choice of tension and groove width combination will be optimal when tension is minimal and strand impregnation is good, but above 100 g at the creel exit, preferably above 200 g, to prevent the formation and / or passage of kinks.

[0112] The inventors have found by chance that when unsized fibrous material is used for the impregnation step in a fluidized bed, control of the residence time in the powder is no longer sufficient to homogeneously impregnate the fibrous material into the thermoplastic polymer matrix, in particular up to the core and with a well-controlled powder (resin) level, and that the pre-impregnation step requires the presence of one or several grooved roller components, in particular one or several grooved rollers, in the fluidized bed with simultaneous control of the tension of said fibrous material at the inlet of the fluidized bed.

[0113] It has also been found that simultaneously controlling the tension of the fibrous material at the inlet of the fluidized bed so that the minimum width of the strand is always greater than the width of the grooves of the roller components, in particular of the grooved cylindrical rollers, allows impregnation of the fibrous material with a thermoplastic polymer matrix, in particular up to the core and with a homogeneous, well-controlled (resin) powder level.

[0114] "Grooved roller component" refers to any system that has grooves that allow the strands to pass through the vessel. The roller component can have any shape, as long as it is grooved and allows the strands to pass through the grooves.

[0115] Advantageously, the size of the groove is slightly smaller than the smallest width of the fiber strand.

[0116] An example of a roller component, which is not limiting of the present invention, is illustrated in detail in FIG.

[0117] This impregnation is done to allow the polymer powder to penetrate to the core of the fiber strands and adhere to the fibers sufficiently to support transport of the powdered strands out of the bath. The powder pre-impregnated strands then pass to a heated calendering apparatus with the possibility of pre-heating before calendering and optional heating after calendering.

[0118] Optionally, this pre-impregnation step can be supplemented by a step of coating the pre-impregnated strands as they leave the bath (20) of pre-impregnation with powder in the fluidized bed (22) and immediately before the step of shaping by calendering. For that purpose, the outlet chamber of the bath (20) (fluidized bed 22) can be connected to a coating device (30) which may include a coating crosshead die head, also described in patent EP 0406067. The polymer to be coated can be the same or different from the polymer powder in the fluidized bed. Preferably, it is of the same nature. Such a coating makes it possible not only to complement the step of pre-impregnation of the fibers, in order to obtain a final volume fraction of polymer in the desired range and to avoid the presence of locally too high fiber levels on the surface of the pre-impregnated strands (which is detrimental for tape welding during the manufacture of composite parts, especially in order to obtain good quality "ready-to-use" fiber material), but also to improve the performance of the composite material obtained.

[0119] The method of the present invention as set forth above is advantageously carried out by a drying process that excludes intentionally charged electrostatic methods.

[0120] The expression "intentional charging" means that a potential difference is applied between the fiber material and the powder. The charge is specifically controlled and amplified. The grains of the powder then impregnate the fiber material by the attraction of the oppositely charged powder to the fibers. By various means (potential difference between two metal electrodes, mechanical friction on metal parts, etc.), it is possible to electrically charge the powder negatively or positively and, conversely (positively or negatively), charge the fibers.

[0121] The method of the invention does not exclude the presence of static charges which may appear in front of or at the bath due to friction of the fibrous material against elements of the implementation device, but which are in any case unintended charges.

[0122] Advantageously, the fibre level in the impregnated fibrous material is between 45 and 65% by volume, preferably between 50 and 60% by volume, in particular between 54 and 60% by volume.

[0123] Below 45% fibre the reinforcement is not interesting in terms of mechanical properties.

[0124] Above 65%, the limits of the method are reached and the mechanical properties are lost again.

[0125] Advantageously, the fibre level in the impregnated fibrous material is between 50 and 60% by volume, in particular between 54 and 60% by volume.

[0126] Advantageously, the residence time in the powder is between 0.01 and 10 seconds, preferably between 0.1 and 5 seconds, in particular between 0.1 and 3 seconds.

[0127] The residence time of the fibrous material in the powder is essential to control the resin content of said fibrous material.

[0128] Below 0.1 seconds the resin content is too low to be able to impregnate the fibres up to the core during the next step of melting the powder.

[0129] Above 10 seconds, the level of polymer matrix impregnating the fibrous material is too high, resulting in poor mechanical properties of the impregnated fibrous material.

[0130] Advantageously, the vessel used in the process of the invention comprises a fluidized bed and said pre-impregnation step is carried out with simultaneous expansion of said strands between the inlet and the outlet of said vessel.

[0131] The expression "the inlet of the vessel" corresponds to a vertical tangent to the edge of the vessel containing the fluidized bed.

[0132] The expression "outlet of said vessel" corresponds to a vertical tangent to the other edge of the vessel containing the fluidized bed.

[0133] Depending on the geometry of the vessel, the distance between its inlet and outlet therefore corresponds to its diameter in the case of a cylinder, to its side in the case of a cube, or to its width or length in the case of a rectangular prism. The expansion consists in isolating as many of the filaments constituting said strand as possible from the other filaments surrounding it in the nearest space, and corresponds to the transverse expansion of the strand.

[0134] In other words, the transverse expansion or width of the strands increases between the inlet of the fluidized bed (or vessel containing the fluidized bed) and the outlet of the fluidized bed (or vessel containing the fluidized bed), thereby allowing homogeneous pre-impregnation of the fibrous material.

[0135] The fluidized bed can be of the open or closed type, in particular of the open type.

[0136] Advantageously, the fluidized bed comprises at least one roller component, said strands being in contact with part or all of the surface of said at least one roller component.

[0137] FIG. 3 depicts a vessel (20) containing a fluidized bed (22) with roller components, the height (82) of which is adjustable.

[0138] The strands (81a) correspond to the pre-impregnated strands which contact part or all of the surface of said at least one roller component and thus pass over at least part or all of the surface of the roller component (82), said system (82) being submerged in a fluidized bed where impregnation takes place, said strands leaving the bath (81b) after a controlled residence time in the powder.

[0139] Said strands (81a) may or may not contact the edge (83a) of the vessel, which edge may be a rotating or stationary roller, or the edge of a parallelepiped.

[0140] Advantageously, said strands (81a) do not contact the rim (83a) of the vessel.

[0141] Advantageously, the rim (83b) of the vessel is a roller, in particular cylindrical and rotating.

[0142] Said strands (81b) may or may not be in contact with the edge (83b) of the vessel, which edge may be a roller, in particular a cylindrical rotating or stationary roller, or the edge of a parallelepiped.

[0143] Advantageously, said strands (81b) abut the rim (83b) of the vessel.

[0144] Advantageously, the rim (83b) of the vessel is a roller, in particular cylindrical and rotating.

[0145] Advantageously, the strands (81a) are in contact with the rim (83a) of the vessel, the rim (83b) of the vessel being a roller, in particular cylindrical and rotating, and the strands (81b) are in contact with the rim (83b) of the vessel, the rim (83b) of the vessel being a roller, in particular cylindrical and rotating.

[0146] Advantageously, said roller components are perpendicular to the direction of said strands.

[0147] Advantageously, said expansion of said strands is at least effected on said at least one roller component.

[0148] Thus, the spreading of the strands takes place mainly at the roller components, but can also take place at the edge of the vessel, if there is contact between the strands and said edge.

[0149] In another embodiment, the at least one roller component is a grooved cylindrical roller having a convex, concave or cylindrical shape.

[0150] A convex shape favors expansion, while a concave shape is unfavorable for expansion, but exists.

[0151] The expression "grooved cylindrical roller" means that the passing strand is partially or totally pressed against the surface of said grooved cylindrical roller, which causes the expansion of said strand.

[0152] Advantageously, said at least one grooved cylindrical roller is cylindrical and the expansion rate of said strand between the inlet and the outlet of said fluidized bed is between 1% and 400%, preferably between 30% and 400%, preferably between 30% and 150%, preferably between 50% and 150%. The expansion rate is defined as (Lf-Li) / Li*100, where Li and Lf are the widths before and after expansion.

[0153] The expansion depends on the fiber material used: for example, the expansion of material made from carbon fibers is much greater than that of linen fibers.

[0154] The expansion also depends on the number, average diameter and cohesion of the fibers or filaments in the strand.

[0155] The diameter of the at least one grooved cylindrical roller is between 3 mm and 500 mm, preferably between 10 mm and 100 mm, in particular between 20 mm and 60 mm.

[0156] Below 3 mm, the deformation of the fibers caused by the grooved cylindrical roller is too large.

[0157] Advantageously, the grooved cylindrical roller is cylindrical, non-ribbed and in particular metallic.

[0158] In the case where the roller component is at least one grooved cylindrical roller, according to a first variant, a single grooved cylindrical roller is present in the fluidized bed and the impregnation is performed at an angle α formed by the strand between the inlet of the grooved cylindrical roller and a vertical tangent of the grooved cylindrical roller. 1 It is held.

[0159] The angle α formed by the strand between the inlet of the grooved cylindrical roller and the vertical tangent of the grooved cylindrical roller 1 This allows the creation of areas where the powder is concentrated and thus causes a "corner effect" where the simultaneous spreading of the strands by said grooved cylindrical roller allows pre-impregnation for a larger strand width and therefore improved pre-impregnation compared to the improved prior art techniques. Thus, in combination with a controlled residence time, allows homogeneous pre-impregnation.

[0160] Advantageously, the angle α 1 includes 0° to 89°, preferably 5° to 85°, preferably 5° to 45°, and preferably 5° to 30°.

[0161] Nevertheless, the angle α, which includes 0 to 5° 1 may cause a risk of mechanical stress leading to fiber breakage, and angles α inclusive of 85°-89° 1 does not create sufficient mechanical force to bring out the "corner effect."

[0162] Therefore, the angle α equals 0° 1 The value of corresponds to vertical fibers. It is clear that the height of the cylindrical grooved cylindrical roller is adjustable and therefore it is possible to position the fibers vertically.

[0163] It would not be outside the scope of the invention if the walls of the vessel were perforated to allow the exit of the strands.

[0164] Advantageously, the rim (83a) of the vessel is provided with rollers, in particular cylindrical rotating rollers, over which the strands pass and thus undergo pre-expansion.

[0165] Advantageously, one or more roller components are present downstream of the vessel containing the fluidized bed, where the expansion begins.

[0166] Advantageously, the expansion starts at said roller component defined above and continues at the edge of the trough (83a).

[0167] The expansion is then at a maximum after passing through a grooved cylindrical roller.

[0168] FIG. 4 illustrates, without limitation, a case in which there is a single cylindrical grooved cylindrical roller and the angle α 1 FIG. 1 depicts an embodiment having a single grooved cylindrical roller with a vessel (20) containing a fluidized bed (22) exhibiting

[0169] The fiber arrows indicate the direction of fiber movement.

[0170] Advantageously, the level of said powder in said fluidized bed is set at at least half the height of said grooved cylindrical roller.

[0171] Angle α 1 It is clear that the "corner effect" caused by the grooved cylindrical roller R enhances the pre-impregnation on one surface, but the expansion of the strands obtained with the grooved cylindrical roller R also allows pre-impregnation on the other surface of the strands. In other words, the pre-impregnation is achieved by the at least one grooved cylindrical roller R 1 The entrance to the grooved cylindrical roller R 1 The angle α formed by the strand with a perpendicular tangent to1 The extension is strengthened on one side of the strand close to the axial extension, but the extension also allows pre-impregnation on the other side.

[0172] Angle α 1 is as defined above.

[0173] According to the second variant, if the roller component is at least one grooved cylindrical roller, then two grooved cylindrical rollers R 1 and R 2 is in the fluidized bed, and the pre-impregnation is performed by the grooved cylindrical roller R 1 and the grooved cylindrical roller R 1 The angle α formed by the strand with the perpendicular tangent of 1 and / or said grooved cylindrical roller R 2 and the grooved cylindrical roller R 2 The angle α formed by the strand with the perpendicular tangent of 2 The grooved cylindrical roller R 1 is the grooved cylindrical roller R 2 , and the strand is passed through roller R 2 It can pass above (Figures 5 and 6) or below (Figures 7 and 8).

[0174] Advantageously, the two grooved cylindrical rollers have the same or different shapes, chosen from convex, concave or cylindrical shapes.

[0175] Advantageously, the two grooved cylindrical rollers are identically cylindrical, in particular metallic.

[0176] The diameters of the two grooved cylindrical rollers can also be the same or different, as defined above.

[0177] Advantageously, the diameter of the two grooved cylindrical rollers is identical.

[0178] Two grooved cylindrical rollers R 1 and R 2can be at the same level with respect to each other and to the bottom of the tank (Figs. 6 and 7) or offset with respect to each other and to the bottom of the tank, and the compression rollers R 1 The height of the grooved cylindrical roller R 2 higher or lower (Figs. 5 and 8).

[0179] Advantageously, the two rollers are at different heights and the strands are 2 When passing above α 2 is 0 to 90°.

[0180] Advantageously, said pre-impregnation is then carried out by means of said grooved cylindrical roller R 1 The angle α formed by the strand between the inlet of the grooved cylindrical roller and the vertical tangent of the grooved cylindrical roller 1 against one side of the strand, and against the grooved cylindrical roller R 2 and the grooved cylindrical roller R 2 The angle α formed by the strand with the perpendicular tangent of 2 on the opposite side of the strand, which is carried out by roller R 2 This is obtained by passing above

[0181] Advantageously, in this embodiment, the strands are spaced apart by respective angles α 1 and α 2 It will be expanded in.

[0182] FIG. 6 illustrates, but is not limited to, two grooved cylindrical rollers R 1 and R 2 and R 1 is R 2 The vessel (20) includes a fluidized bed (22) in which two cylindrical grooved rollers are present side by side at the same level, and the strand is then rolled by the grooved cylindrical rollers R 1 and R 2 It comes out from between.

[0183] In this case, the angle α 2is equal to 0, and the strand is moved toward the roller R 2 passes above.

[0184] The fiber arrows indicate the fiber pass direction.

[0185] Alternatively, the strand is rolled on the grooved cylindrical roller R 1 and R 2 and passing through the inlet between the grooved cylindrical roller R 2 after coming into contact with part or all of the surface.

[0186] Advantageously, the strand is fed at its inlet by the grooved cylindrical roller R 1 contact with part or all of the surface of the roller R 2 Below the grooved cylindrical roller R 2 After contacting all or part of the surface of the grooved cylindrical roller R 2 The angle α 2 is the grooved cylindrical roller R 2 and the grooved cylindrical roller R 2 The angle α 2 =90°.

[0187] Therefore, the pre-impregnation is performed by the grooved cylindrical roller R 1 The angle α formed by the strand between the inlet of the grooved cylindrical roller and the vertical tangent of the grooved cylindrical roller 1 against one side of the strand, and against the grooved cylindrical roller R 2 and the grooved cylindrical roller R 2 The angle α formed by the strand with the perpendicular tangent of 2 on the same face of the strand, but by extension it is possible to pre-impregnate the other face.

[0188] Advantageously, the strands in this embodiment have respective angles α 1 and α 2 It will be expanded in.

[0189] Figure 7 shows two grooved cylindrical rollers R 1 and R 2 1 shows an exemplary embodiment having the same levels as each other.

[0190] According to another embodiment of the second variant, when there are two grooved cylindrical rollers, the two grooved cylindrical rollers R 1 and R 2 The distance between the two grooved cylindrical rollers R is from 0.15 mm to a length equivalent to the maximum dimension of the tank, preferably 10 mm to 50 mm. 1 and R 2 The height difference between is 0 to a height corresponding to the maximum height of the tank minus the diameter of the two grooved cylindrical rollers, preferably 0.15 mm to a height corresponding to the maximum height of the tank minus the diameter of the two grooved cylindrical rollers, more preferably 10 mm to 300 mm, R 2 is the upper grooved cylindrical roller.

[0191] Advantageously, when two grooved cylindrical rollers are present and at the same level with each other, the level of said powder in said fluidized bed is set at at least half the height of said two grooved cylindrical rollers.

[0192] FIG. 8 illustrates, but is not limited to, two grooved cylindrical rollers R 1 and R 2 and R 1 is R 2 , the vessel (20) includes a fluidized bed (22) in which two cylindrical grooved rollers are at different levels and are spaced apart by an angle α 1 and α 2 Shows.

[0193] Grooved cylindrical roller R 1 and R 2 Although the diameters of the grooved cylindrical rollers R are shown to be the same in Figs. 5, 6, 7 and 8, the diameters of each grooved cylindrical roller R may vary. 1The diameter of the grooved cylindrical roller R is within the range defined above. 2 It can be bigger or smaller.

[0194] Advantageously, the diameter of the two grooved cylindrical rollers is the same.

[0195] Grooved cylindrical roller R 1 Compression roller R 2 A larger value would not be beyond the scope of the present invention.

[0196] According to a third variant, two grooved cylindrical rollers are present at different levels and at least one third grooved cylindrical roller R 3 There is also a grooved cylindrical roller R 1 and R 2 It is installed between (Figure 9).

[0197] Advantageously, the strand is fed at its inlet by the grooved cylindrical roller R 1 and then the grooved cylindrical roller R 3 and the grooved cylindrical roller R 2 after coming into contact with part or all of the surface.

[0198] Advantageously, said pre-impregnation is carried out by rolling said at least one grooved cylindrical roller R against one side of said strand. 1 and the grooved cylindrical roller R 1 The angle α formed by the strand with the perpendicular tangent of 1 and the grooved cylindrical roller R 3 The angle α formed by the strand with the perpendicular tangent of 3 and the grooved cylindrical roller R against the other surface. 2 The angle α formed by the strand with the perpendicular tangent of 2 It is held.

[0199] Advantageously, two grooved cylindrical rollers are present at different levels and at least one third grooved cylindrical roller R 3 When also present, said at least one grooved cylindrical roller R 2 and the grooved cylindrical roller R 2 The angle α formed by the strand with the perpendicular tangent of 2 is between 180° and 45°, particularly between 120° and 60°.

[0200] Advantageously, the angle α 3 is between 0° and 180°, advantageously between 45° and 135°.

[0201] FIG. 9 illustrates, without limitation, two grooved cylindrical rollers R 1 and R 2 , as well as a third grooved cylindrical roller R 3 The present invention describes an embodiment of a vessel (20) including a fluidized bed (22) having R 1 is R 2 precedes the angle α 1 , α 2 and α 3 is shown.

[0202] Grooved cylindrical roller R 1 , R 2 and R 3 Although the diameters of the cylindrical grooved rollers are shown to be the same in FIG. 9, the diameter of each cylindrical grooved roller can be different, or two of the cylindrical grooved rollers can have the same diameter and the third one can have a different, larger or smaller diameter within the ranges defined above.

[0203] Advantageously, the diameter of the three grooved cylindrical rollers is the same.

[0204] Advantageously, in this third variant, the second control of the expansion of the strand is achieved by means of a grooved cylindrical roller R 3 The third control of expansion is the compression roller R 3 It is held.

[0205] In this third variant the residence time is as defined above.

[0206] Advantageously, in this third variant, the level of the powder in the fluidized bed is at least equal to the grooved cylindrical roller R 2 is placed at half the height of the

[0207] In this third variant, the strand is fed into the grooved cylindrical roller R 1 and then the grooved cylindrical roller R 2 and the grooved cylindrical roller R 3 It would not be outside the scope of the invention if the particles emerged after contacting some or all of the surface of the substrate.

[0208] According to one advantageous embodiment, the invention relates to a method as defined above, characterized in that a single thermoplastic polymer matrix is ​​used and that the thermoplastic polymer powder is fluidizable.

[0209] The term "fluidizable" means that the air flow rate applied to the fluidized bed is between the minimum fluidization flow rate (Umf) and the minimum bubbling flow rate (Umf) shown in FIG.

[0210] Below the minimum fluidization flow rate, there is no fluidization, the polymer powder particles fall into the bed and are no longer in suspension and the process according to the invention cannot be carried out.

[0211] Above a minimum bubbling flow rate, powder particles fly away and a constant fluidized bed composition can no longer be maintained.

[0212] Advantageously, the particles have a volume diameter D90 of between 50 and 500 μm, advantageously between 120 and 300 μm.

[0213] Advantageously, the particles have a volume diameter D10 of between 5 and 200 μm, advantageously between 35 and 100 μm.

[0214] Advantageously, the particles of the powder have a volume diameter in the ratio D90 / D10 or between 1.5 and 50, advantageously between 2 and 10.

[0215] Advantageously, the particles of the thermoplastic polymer powder have a mean volume diameter D50 of between 30 and 300 μm, in particular between 50 and 200 μm and more particularly between 70 and 200 μm.

[0216] The volume diameters of the particles (D10, D50 and D90) are defined according to standard ISO 9276:2014.

[0217] "D50" corresponds to the volume mean diameter, ie, the particle size value that divides a examined population of particles exactly in half.

[0218] "D90" corresponds to the 90% value of the integral curve of the particle size distribution by volume.

[0219] "D10" corresponds to the size of 10% of the particle's volume.

[0220] According to another embodiment of the method of the invention, a creel is present before the vessel containing the fluidized bed in order to control the tension of said strand at the inlet of the vessel containing the fluidized bed.

[0221] Optionally, in a method according to the invention, one or more roller components are present after the vessel containing the fluidized bed.

[0222] Optionally, grooved rollers can be used at the inlet and outlet of the vessel containing the fluidized bed.

[0223] heating process

[0224] In another embodiment, the invention is characterized in that the method as defined above further comprises, after pre-impregnation, at least one step of heating the thermoplastic matrix making it possible to melt or to maintain said thermoplastic polymer in the molten state,

[0225] At least one heating step is carried out by at least one heat-conducting or non-heat-conducting roller component (E) and at least one heating system, excluding a heating calendar;

[0226] The strands are in contact with a part or the whole of the surface of the at least one roller component (E) and run part or the whole above the surface of the at least one roller component (E) at the level of the heating system.

[0227] It would not be outside the scope of the invention if the roller component (E) is placed in an oven that includes a heating system, e.g., IR heating, however, the roller component is not placed directly under the heating element, e.g., IR heating. It would not be outside the scope of the invention if the oven included a convection heating mode and an IR heating system.

[0228] Also, if the oven or the roller component (E) placed in the oven environment is equipped with autonomous heating means, such as, for example, resistors allowing heating of the roller component (E) independently of the irradiation from IR lamps and the natural convection of the oven, it would not be outside the scope of the invention if the polymer present in the bands or strands was still in the molten state when it arrived in contact with the roller component, in view of the line speed.

[0229] The height between the heating system and the roller component is between 1 and 100 cm, preferably between 2 and 30 cm, in particular between 2 and 10 cm.

[0230] The first heating step may be consecutive with the pre-impregnation step, or alternatively, other steps may be between the pre-impregnation step and the heating step.

[0231] However, the first step of implementation by a heating system with at least one roller component (E) does not correspond to a heated calender and is always carried out before the calendering step necessary to smooth and shape the band.

[0232] Advantageously, said first heating step immediately follows a pre-impregnation step, the expression "immediately following" meaning that there are no intervening steps between the pre-impregnation step and said heating step.

[0233] Advantageously, the pre-impregnation step is immediately followed by a single heating step.

[0234] Advantageously, said at least one heating system is selected from infrared bulbs, UV bulbs and, in case the roller components are thermally conductive, convection heating.

[0235] The textile material is in contact with the roller component and the heating system, and since the roller component is conductive, the heating system also works by conduction.

[0236] Advantageously, said at least one heating system is chosen from infrared bulbs.

[0237] Advantageously, when the roller component is non-thermally conductive, said at least one heating system is selected from microwave heating, laser heating and radio frequency (HF) heating.

[0238] The unheated, non-thermally conductive roller component (E) does not absorb the wavelengths of microwave, laser or HF heating systems.

[0239] Advantageously, said at least one heating system is selected from microwave heating.

[0240] Advantageously, said at least one roller component (E) is a compression roller R'i of convex, concave or cylindrical shape.

[0241] It should be noted that the compression rollers corresponding to the roller components (E) and those used for the pre-impregnation step can be identical or different in terms of material or shape and their properties (diameter, length, width, height, etc. depending on the shape).

[0242] A convex shape favors expansion, while a concave shape is unfavorable for expansion, but exists.

[0243] At least one roller component (E) can also have an alternating convex and concave shape, in which case the passage of the strands over a convex compression roller causes the strands to expand, while the passage of the strands over a concave compression roller causes the strands to retract, etc., making it possible to improve the uniformity of the impregnation, especially up to the core, if necessary.

[0244] The expression "compression roller" means that the passing strand is partially or totally pressed against the surface of said compression roller, which causes expansion of said strand.

[0245] The rollers can be rotationally controlled or stationary.

[0246] They are grooved and the bottom of the grooves may be smooth or striated.

[0247] Molding process

[0248] Optionally, a step of shaping said strands or said parallel strands of impregnated fibrous material is performed.

[0249] The calendar system described in WO2015 / 121583 can be used.

[0250] Advantageously, it is carried out by calendering in the form of a single unidirectional band or sheet or of a plurality of parallel unidirectional bands or sheets using at least one heated calender, said heated calender comprising in the latter case a plurality of calender grooves, preferably up to 200 calender grooves, with the number of said bands and the pressure and / or separation between the rollers of said calender being regulated by a closed-loop control system.

[0251] This step is always carried out after the heating step if there is only one, or during the first and second heating steps if both are present.

[0252] Advantageously, the calendering step is carried out using a number of heated calenders mounted in parallel and / or in series relative to the direction of movement of the fibre strands.

[0253] Advantageously, said heating calender comprises an integrated induction or microwave heating system, preferably a microwave heating system, in combination with the presence of a carbon filler in said thermoplastic polymer or mixture of thermoplastic polymers.

[0254] According to another embodiment, there is a belt press between the heating system and the calender.

[0255] According to yet another embodiment, there is a heating nozzle between the heating system and the calender.

[0256] According to another embodiment, there is a belt press between the heating system and the calendar, and there is a heating nozzle between the belt press and the calendar.

[0257] Advantageously, the step of shaping said parallel strands of pre-impregnated fibrous material comprises: It is carried out by calendering into the form of a single unidirectional band or sheet or a number of parallel unidirectional bands or sheets using at least one heated calender, in the latter case said heated calender comprising a number of calender grooves, preferably up to 300 calender grooves, with the number of said bands and the pressure and / or separation between the rollers of said calender being regulated by a closed loop control system.

[0258] Advantageously, the calendering step is carried out using a number of heated calenders mounted in parallel and / or in series relative to the direction of movement of the fibre strands.

[0259] Advantageously, said heating calender comprises an integrated induction or microwave heating system, preferably a microwave heating system, in combination with the presence of a carbon filler in said thermoplastic polymer or mixture of thermoplastic polymers.

[0260] In one embodiment, the heating calendar is combined with a complementary heating device placed before and / or after the (each) calendar, in particular a microwave or induction heating device or an infrared IR or laser heating device in combination with the presence of a carbon-based filler in the polymer or the mixture of polymers, or a device for heating by direct contact with another heat source such as a flame or hot gas.

[0261] In another embodiment, the pre-impregnation step is complemented by a step of coating the single strand or the parallel strands after pre-impregnation with a powder with a molten thermoplastic polymer, which may be the same or different from the polymer in powder form in the fluidized bed, said coating step being carried out before the calendaring step, said molten polymer being preferably of the same type as the polymer in powder form in the fluidized bed, and preferably said coating being achieved by cross-head die extrusion on the single strand or the parallel strands.

[0262] According to another aspect, the invention relates to a unidirectional band or sheet of impregnated fibrous material, in particular a band or sheet wound on a spool, characterized in that it is obtained using the method defined above.

[0263] Advantageously, the band or sheet has a width (l) and thickness (ep) suitable for robotic deposition in the manufacture of three-dimensional parts, preferably having a width (l) of at least 5 mm, which may be up to 600 mm, preferably between 50 and 600 mm, even more preferably between 50 and 300 mm.

[0264] Robotic deposition may or may not involve slitting.

[0265] Advantageously, the thermoplastic polymer of the band or sheet is a polyamide, in particular an aliphatic polyamide such as PA6, PA11, PA12, PA66, PA46, PA610, PA612, PA1010, PA1012, PA11 / 1010 or PA12 / 1010, or a semi-aromatic polyamide such as PA MXD6 and PA MXD10, or a polyamide such as PA6 / 6T, PA66 / 6T, PA6I / 6T, PA MPMDT / 6T, PA MXDT / 6T, PA PA11 / 10T, PA11 / 6T / 10T, PA MXDT / 10T, PA MPMDT / 10T, PA BACT / 10T, PA BACT / 6T, PA BACT / 10T / 6T, PA Selected from BACT / 6T / 11, PA11 / BACT / 10T, PA11 / MPMDT / 10T and PA11 / MXDT / 10T, PVDF, PEEK, PEKK and PEI or mixtures thereof.

[0266] According to another aspect, the invention relates to the use of the method defined above for the manufacture of calibration bands or sheets suitable for the manufacture of three-dimensional composite parts by automated deposition of said bands or sheets by means of a robot.

[0267] According to another aspect, the invention relates to the use of a band or sheet of impregnated fibrous material as defined above in the manufacture of a three-dimensional composite part.

[0268] Said impregnated band is thus obtained from a pre-impregnated band after the heating step described above.

[0269] Advantageously, said manufacture of said composite parts relates to the fields of transportation, in particular automotive, oil and gas, in particular marine, gas storage, civil or military aviation, aerospace, offshore, railway; renewable energy, in particular wind energy, tidal energy, energy storage devices, solar panels; insulation panels; sports and recreation, health and medicine, security and electronics.

[0270] According to another of its aspects, the invention relates to a three-dimensional composite part, characterized in that it results from the use of at least one unidirectional band of impregnated fibre material as defined above.

[0271] Advantageous embodiments of the method according to the invention

[0272] Advantageously, the fibre material is chosen from carbon fibres and glass fibres.

[0273] Advantageously, the thermoplastic polymer used to impregnate the carbon fibres is selected from polyamides, in particular aliphatic polyamides such as PA11, PA12, PA11 / 1010 or PA12 / 1010, or semi-aromatic polyamides, in particular PA MXD6 and PA MXD10, or those selected from PA6 / 6T, PA66 / 6T, PA6I / 6T, PA MPMDT / 6T, PA MXDT / 6T, PA PA11 / 10T, PA11 / 6T / 10T, PA MXDT / 10T, PA MPMDT / 10T, PA BACT / 10T, PA BACT / 6T, PA BACT / 10T / 6T, PA BACT / 6T / 11, PA11 / BACT / 10T, PA11 / MPMDT / 10T and PA11 / MXDT / 10T, PVDF, PEEK, PEKK and PEI or mixtures thereof.

[0274] Advantageously, the thermoplastic polymer used to impregnate the glass fibres is selected from polyamides, in particular aliphatic polyamides such as PA11, PA12, PA11 / 1010 or PA12 / 1010, or semi-aromatic polyamides, in particular PA MXD6 and PA MXD10, or those selected from PA6 / 6T, PA66 / 6T, PA6I / 6T, PA MPMDT / 6T, PA MXDT / 6T, PA PA11 / 10T, PA11 / 6T / 10T, PA MXDT / 10T, PA MPMDT / 10T, PA BACT / 10T, PA BACT / 6T, PA BACT / 10T / 6T, PA BACT / 6T / 11, PA11 / BACT / 10T, PA11 / MPMDT / 10T and PA11 / MXDT / 10T, PVDF, PEEK, PEKK and PEI or mixtures thereof.

[0275] Advantageously, the fibre level in said impregnated fibrous material consisting of carbon or glass fibres is between 45 and 65% by volume, preferably between 50 and 60% by volume, in particular between 54 and 60% by volume. [Brief description of the drawings]

[0276] [Figure 1] 1 shows a schematic diagram of an installation for carrying out the method for producing a pre-impregnated fibrous material according to the invention; [Diagram 2] 2 shows a partial schematic diagram of two rollers constituting the calender used in the installation of FIG. 1; [Diagram 3] A vessel (20) is described that includes a fluidized bed (22) with a grooved roller component, the height of which (82) is adjustable. The inlet edge of the vessel is provided with rotating rollers 83a over which the strands 81a pass, and the outlet edge of the vessel is provided with rotating rollers 83b over which the strands 81b pass. The roller grooves are visible only in front or top view, since the rollers are perpendicular to the direction of strand travel. [Figure 4]An embodiment with a single grooved cylindrical roller is described, where the vessel (20) contains a fluidized bed (12) with a single grooved cylindrical roller (24) and angle α1 is shown. The fiber arrow indicates the direction of fiber movement. The roller is perpendicular to the direction of strand movement, so the roller grooves are only visible in a front or top view. [Diagram 5] A non-limiting embodiment is shown having two grooved cylindrical rollers R1 and R2, where R1 precedes R2, and the vessel (20) contains a fluidized bed (22) in which the two cylindrical grooved rollers are at different heights relative to the bottom of the vessel (R2 at height H2 above R1 at height H1), and angles α1 and α2 are shown. The arrows on the fiber rovings indicate the direction of fiber passage. [Figure 6] An exemplary embodiment is shown having a vessel (20) containing a fluidized bed (22), where two grooved cylindrical rollers R1 and R2 are cylindrical, side-by-side at the same level relative to each other, exhibiting angles α1 and α2=0°, and the strand passes between the two rollers. [Figure 7] An exemplary embodiment is shown having a vessel (20) containing a fluidized bed (22), where two grooved cylindrical rollers R1 and R2 are cylindrical, side by side at the same level relative to each other, exhibiting angles α1 and α2=90°, with the strand passing under R2. [Figure 8] An exemplary embodiment is shown having a vessel (20) containing a fluidized bed (22), where two grooved cylindrical rollers R1 and R2 are at different levels, R1 precedes R2 and exhibits angles α1 and α2, and the strand passes under R2. [Figure 9] An embodiment is shown having a vessel (20) containing a fluidized bed (22) with two grooved cylindrical rollers R1 and R2 (R1 precedes R2) and a grooved cylindrical roller R3, with angles α1, α2 and α3 shown. [Figure 10]Photograph obtained by scanning electron microscopy of a cross-section of a ¼″ carbon fiber band obtained from a 12K carbon fiber strand homogeneously pre-impregnated with PA MPMDT / 10T polyamide powder (67 / 33 mol%) having D50=115 μm according to the method of WO2018115736 (as described in Comparative Example 1), using a non-grooved (smooth) roller and a low tension of 800 g at the entrance to the fluidized bed. The fiber is then impregnated to the core with the resin after melting of the powder present in the pre-impregnated strand, and after heating and passing over a series of roller components, is subsequently calendered to form the final band. Image analysis is performed on several statistically representative images of the band, giving a porosity level of 3% except at the band edges. [Figure 11] 1 shows the evolution of the weight percentage of MPMDT / 10T impregnated in the strands as a function of time from Comparative Example 1. [Figure 12] 1 shows a photograph obtained by scanning electron microscopy of a cross section of a ¼″ carbon fiber band obtained from a 12K carbon fiber strand homogeneously pre-impregnated with PA MPMDT / 10T polyamide powder (67 / 33 mol%) having D50=115 μm according to the method of the invention and as described in comparative example 2), i.e. using grooved rollers and a low tension of 800 g at the entrance of the fluidized bed. The fibers are then impregnated to the core with the resin after melting of the powder present in the pre-impregnated strand and, after heating and passing over a series of roller components, are subsequently calendered to form the final band. After heating and calendering with grooved rollers and a low tension of 800 g at the entrance of the fluidized bed of example 2). From the image analysis, a porosity level of 1.5% is obtained, except at the edges of the tape. [Figure 13] 1 shows the evolution of the weight percentage of impregnated MPMDT / 10T in the strands as a function of time from Comparative Example 2. [Figure 14] Fluidization as a function of air velocity: The air flow rate applied to the fluidized bed must be between the minimum fluidization flow rate (Umf) and the minimum bubbling flow rate (Umf). EXAMPLES

[0277] The following examples provide non-limiting illustrations of the scope of the invention.

[0278] Comparative Example 1: General procedure for pre-impregnation of fibrous material (unsized carbon fibres) with MPMDT / 10T powder (67 / 33 mol%) in a fluidised bed with a single smooth cylindrical roller and using low tension of the strands (800 g) at the inlet of the fluidised bed

[0279] The procedure was as follows: - Smooth cylindrical roller, diameter 25 mm, in a tank (L=500mm, l=500mm, H=600mm) - Strand tension at the inlet of the fluidized bed: 800g - 0.3 second residence time in powder - Angle α 1 25° - 12K AS4 Hexcel carbon fiber strands have an expansion of approximately 100% (i.e. width multiplied by 2) - D50=115μm, for MPMDT / 10T powder (D10=49μm, D90=207μm) - The rim of the tub is equipped with stationary rollers.

[0280] According to this operating procedure, the MPMDT / 10T polyamide powder with the particle size defined above is used to homogeneously pre-impregnate a fiber material (12K carbon fiber strands), the bands obtained from this pre-impregnated strands are subsequently calendered after melting of the powder and passing over a series of roller components, which are shown in Figure 10, to obtain 1 / 4" bands.

[0281] The results obtained show that the impregnated polymer level is not stable over time (see FIG. 11). The strand width at the exit of the fluidized bed varies.

[0282] Example 2: General procedure for pre-impregnation of fibrous material (unsized carbon fibres) with polyamide powder in a fluidised bed with a single grooved cylindrical roller and using low tension (800 g) of the strands at the inlet of the fluidised bed

[0283] The procedure was as follows: - grooved cylindrical roller in the trough (L=500mm, l=500mm, H=600mm), Diameter 25mm at bottom of groove, groove width 5mm - Strand tension at the entrance to the fluidized bed: 800g - 0.3 second residence time in powder - Angle α 1 25° - Unsized 12K AS4 Hexcel carbon fiber strands with approximately 100% expansion (i.e. width multiplied by 2) - D50=115μm, for MPMDT / 10T powder (67 / 33mol%) (D10=49μm, D90=207μm) - The rim of the tub is equipped with stationary rollers.

[0284] According to this procedure, the MPMDT / 10T polyamide powder with the particle size defined above is used to homogeneously pre-impregnate a fiber material (12K carbon fiber strands), and the bands obtained from these pre-impregnated strands are subsequently calendered after melting of the powder and passing over a series of roller components, which are shown in FIG. 12, to obtain a 1 / 4" tape.

[0285] When the grooved roller is in the powder, the impregnated polymer level remains stable over time by using low tension on the fibers at the fluid bed entrance (see FIG. 13).

[0286] Furthermore, due to the low tension applied to the fibers at the fluidized bed inlet, no fuzz formation is observed prior to pre-impregnation, thus promoting tape health.

[0287] This demonstrates the effectiveness of the method of pre-impregnating dry powder in a fluidized bed using a grooved cylindrical roller with unsized fibers as opposed to a smooth roller, residence time in the powder and control of tension.

[0288] Example 3: Determining the porosity level by image analysis

[0289] The porosity was determined by image analysis for 1 / 2" carbon fiber strands impregnated with MPMDT / 10T. It is 5%.

[0290] Example 4: Determination of the relative deviation of the porosity level between theoretical and experimental density (general method) a) Required data: - Density of the thermoplastic matrix - Fiber density - Reinforcement weight: For example, linear mass (g / m) for 1 / 4 inch tape (from a single strand) - areal density (g / m2) for e.g. wider tapes or fabrics 2 ) b) Measurements to be taken: The number of samples should be at least 30 in order for the results to be representative of the material studied. Measurements to be taken: - Size of sample taken: Length (if linear mass is known) Length and width (if areal density is known) - Experimental density of samples taken: Mass measurement in air and water - The measurement of the fiber level is determined according to ISO 1172:1999 or by thermogravimetric analysis (TGA) as determined, for example, in the document B. Benzler, Applikationslabor, Mettler Toledo, Giesen, UserCom 1 / 2001.

[0291] Measurement of carbon fiber level may be determined according to ISO 14127:2008.

[0292] Determination of theoretical mass fiber level: a) Determination of the theoretical mass fiber level: TIFF2025041649000002.tif14170, where m 1 is the linear mass of the tape, L is the sample length, Me air is the mass of the sample measured in air.

[0293] It is assumed that variations in mass fiber level are directly related to variations in matrix level without considering variations in the amount of fiber in the reinforcement. b) Determination of the theoretical density: TIFF2025041649000003.tif20170

[0294] where d m and d f are the densities of the matrix and the fibers, respectively.

[0295] The theoretical density thus calculated is the density that would be attained if there was no porosity in the sample. c) Porosity assessment: Porosity is the relative deviation between theoretical and experimental density.

Claims

1. A method for manufacturing a pre-impregnated fibrous material comprising a fibrous material made of continuous fibres and at least one thermoplastic polymer matrix, characterized in that said pre-impregnated fibrous matrix is ​​produced as a single unidirectional band or as a number of unidirectional parallel bands, and in that it comprises a step of pre-impregnating, particularly homogeneously, said fibrous material still in the form of a strand (81a) or of several parallel strands with said at least one thermoplastic polymer matrix in powder form, said pre-impregnation step being carried out by a dry process in a vessel (20) comprising a fluidised bed (22) comprising at least one grooved roller component (82), the strands (81 a) contact a portion or all of a surface of the at least one grooved roller component (82), the strands (81 a) comprising 0.1% by weight or less of a sizing; A method in which the proportion of said at least one thermoplastic polymer matrix in said fibrous material is controlled by controlling the residence time of said fibrous material in the powder as said strands (81 a) pass through the fluidized bed and by constant control of the tension of said strands (81 a).

2. 2. The method of claim 1, characterized in that the strands (81a) are unsized.

3. 3. The method according to claim 1 or 2, characterized in that the tension of the strand (81a) when it passes through the fluidized bed is 1000 g or less.

4. 4. The method according to claim 3, characterized in that the tension of the strand (81a) when it passes through the fluidized bed is between 100 and 1000 g, in particular between 200 and 1000 g, more particularly between 300 and 850 g.

5. 5. The method according to any one of claims 1 to 4, characterized in that the minimum width of the strands (81a) is greater than the width of the grooves of the grooved roller component.

6. 6. The method according to any one of claims 1 to 5, characterized in that the pre-impregnation step is carried out with simultaneous expansion of the strands (81a) between the inlet and the outlet of the fluidized bed (22).

7. 7. The method according to claim 1, wherein the particles of the thermoplastic polymer powder have a volume-average diameter D50 of 30 to 300 μm, in particular 50 to 200 μm and more particularly 70 to 200 μm.

8. A method according to any one of the preceding claims, characterised in that the fibre level in the impregnated fibrous material is from 45 to 65% by volume, preferably from 50 to 60% by volume, in particular from 54 to 60% by volume.

9. 9. The method according to claim 1, characterized in that the residence time in the powder is from 0.01 to 10 seconds, preferably from 0.1 to 5 seconds, in particular from 0.1 to 3 seconds.

10. 10. The method according to any one of claims 1 to 9, characterized in that the grooved roller component is a grooved cylindrical roller and the expansion percentage of the strands (81a) between the inlet and the outlet of the vessel is between 1% and 400%, preferably between 30% and 400%, preferably between 30% and 150%, preferably between 50% and 150%.

11. A single grooved cylindrical roller is present in the fluidized bed (22), and the impregnation is performed by the angle α formed by the strands (81a) between the inlet of the grooved cylindrical roller and a vertical tangent to the grooved cylindrical roller. 1 11. The method according to claim 10, characterized in that it is carried out at

12. Angle α 1 is between 0° and 89°, preferably between 5° and 85°, preferably between 5° and 45°, preferably between 5° and 30°.

13. Two grooved cylindrical rollers R 1 and R 2 is present in the fluidized bed (22), and the pre-impregnation is performed by the grooved cylindrical roller R 1 The angle α formed by the strand (81a) between the inlet of the grooved cylindrical roller and the vertical tangent of the grooved cylindrical roller 1 and / or the grooved cylindrical roller R 2 and the grooved cylindrical roller R 2 The angle α formed by the strand (81a) with the perpendicular tangent of 2 and the grooved cylindrical roller R 1 is the grooved cylindrical roller R 2 (in the direction in which the process proceeds) and said strand (81a) is 2 11. The method according to claim 10, characterized in that the method can be performed by passing above or below the

14. Two grooved cylindrical rollers R 1 and R 2 and the distance between the two grooved cylindrical rollers R 1 and R 2 and the height difference between the two grooved cylindrical rollers is from 0 to a height corresponding to the maximum height of the tank (20) minus the diameter of the two grooved cylindrical rollers, preferably from 0.15 mm to a height corresponding to the maximum height of the tank (20) minus the diameter of the two grooved cylindrical rollers, more preferably from 10 mm to 300 mm, R 2 14. The method of claim 13, characterized in that is an upper grooved cylindrical roller.

15. 15. The method according to any one of claims 1 to 14, characterized in that a single thermoplastic polymer matrix is ​​used and the thermoplastic polymer powder is fluidizable.

16. after pre-impregnation, further comprising at least one step of heating the thermoplastic matrix, which allows said thermoplastic polymer to melt or to remain in a molten state, At least one heating step is carried out by at least one heat-conducting or non-heat-conducting roller component (E) and at least one heating system, excluding a heating calendar; 16. The method according to any one of claims 1 to 15, characterized in that the strand contacts partly or entirely with the surface of the at least one roller component (E) and runs partly or entirely above the surface of the at least one roller component (E) at the level of the heating system.

17. 17. The method according to any one of claims 1 to 16, further comprising a step of shaping the strand or the parallel strands of the pre-impregnated fibrous material by calendering them into the form of a single unidirectional band or a plurality of parallel unidirectional bands or sheets using at least one heated calender, in the latter case, the heated calender comprising a plurality of calendering grooves, preferably up to 300 calendering grooves, according to the number of bands and the pressure and / or separation between the rollers of the calender being regulated by a closed loop control system.

18. 18. Method according to claim 17, characterized in that the calendering step is carried out using a plurality of heated calenders (51, 52, 53) mounted in parallel and / or in series with respect to the moving direction of the fibre strand (81a).

19. 19. The method according to claim 17 or 18, characterized in that the heating calender (51, 52, 53) comprises an integrated induction or microwave heating system, preferably a microwave heating system, in combination with the presence of a carbon-based filler in the thermoplastic polymer or mixture of thermoplastic polymers.

20. 20. The method according to any one of claims 17 to 19, characterized in that the heating calender (51, 52, 53) is combined with an additional rapid heating device (41, 42, 43) placed before and / or after the (respective) calender (51, 52, 53), in particular a microwave heating device or an induction heating device in combination with the presence of a carbon-based filler in the polymer or the mixture of polymers, or an infrared IR or laser heating device, or a device for heating by direct contact with another heat source such as a flame or hot gas.

21. 21. The method according to any one of claims 1 to 20, characterized in that the pre-impregnation step is complemented by a step of coating the single strand (81 a) or the parallel strands after pre-impregnation with a powder with a molten thermoplastic polymer, which may be the same or different from the polymer in powder form in the fluidized bed (22), said coating step being carried out before the calendaring step, said molten polymer being preferably of the same type as the polymer in powder form in the fluidized bed (22), and preferably said coating being achieved by cross-head die extrusion on the single strand (81 a) or the parallel strands.

22. 22. The method according to any one of claims 1 to 21, characterized in that the thermoplastic polymer further comprises a carbonaceous filler, in particular carbon black or a carbon nanofiller, preferably selected from carbonaceous nanofillers, in particular graphene and / or carbon nanotubes and / or carbon nanofibrils or mixtures thereof.

23. 23. The method of any one of claims 1 to 22, characterized in that the thermoplastic polymer further comprises a liquid crystal polymer or a cyclized poly(butylene terephthalate), or a blend containing the same as an additive.

24. The at least one thermoplastic polymer may be selected from the group consisting of: polyaryletherketones (PAEK), in particular poly(etheretherketones) (PEEK); polyaryletherketoneketones (PAEKK), in particular polyetherketoneketones (PEKK); aromatic polyetherimides (PEI); polyarylsulfones, in particular polyphenylenesulfones (PPSU); polyarylsulfides, in particular polyphenylenesulfide (PPS); polyamides (PA), in particular aromatic polyamides optionally modified with urea units; PEBA, polyacrylates, in particular polymers.

24. The method according to claim 1, characterized in that the polymer is selected from: polymethylmethacrylate (PMMA); polyolefins, in particular polypropylene, polylactic acid (PLA), polyvinyl alcohol (PVA), and fluorinated polymers, in particular polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE) or polychlorotrifluoroethylene (PCTFE); and mixtures thereof, in particular mixtures of PEKK and PEI, preferably in an amount of from 90-10% by weight to 60-40% by weight, in particular from 90-10% by weight to 70-30% by weight.

25. 25. The method according to claim 24, characterized in that the at least one thermoplastic polymer is a polymer having a glass transition temperature Tg > 80°C or a semi-crystalline polymer having a melting point Tm > 150°C.

26. 26. The method according to any one of claims 1 to 25, characterized in that the fibrous material comprises continuous fibres selected from carbon, glass, silicon carbide, basalt, silica, natural fibres, in particular flax or hemp, lignin, bamboo, sisal, silk or cellulose, in particular viscose, or amorphous thermoplastic fibres having a glass transition temperature Tg higher than the Tg of the polymer or polymer mixture when it is amorphous or higher than the Tm of the polymer or polymer mixture when it is semi-crystalline, or semi-crystalline thermoplastic fibres having a melting temperature Tm higher than the Tg of the polymer or polymer mixture when it is amorphous or higher than the Tm of the polymer or polymer mixture when it is semi-crystalline, or a mixture of two or more of said fibres, preferably a mixture of carbon fibres, glass or silicon carbide, in particular carbon fibres.

27. A unidirectional band of impregnated fibre material, in particular a band wound on a spool, characterized in that it is obtained by a method according to any one of claims 16 to 26.

28. 28. The band according to claim 27, having a width (l) and thickness (ep) suitable for robotic applications in the manufacture of three-dimensional workpieces without the need for slitting, characterized in that the width (l) is at least 5 mm and not more than 400 mm, preferably between 5 mm and 50 mm, even more preferably between 5 mm and 15 mm.

29. The thermoplastic polymer is in particular an aliphatic polyamide, such as PA6, PA11, PA12, PA66, PA46, PA610, PA612, PA1010, PA1012, PA11 / 1010 or PA12 / 1010, or a semi-aromatic polyamide, such as PA MXD6 and PA MXD10, or PA6 / 6T, PA66 / 6T, PA6I / 6T, PA MPMDT / 6T, PA MXDT / 6T, PA PA11 / 10T, PA11 / 6T / 10T, PA MXDT / 10T, PA MPMDT / 10T, PA BACT / 10T, PA BACT / 6T, PA BACT / 10T / 6T, PA 29. The band according to claim 27 or 28, which is selected from those selected from BACT / 6T / 11, PA11 / BACT / 10T, PA11 / MPMDT / 10T and PA11 / MXDT / 10T, PVDF, PEEK, PEKK and PEI or mixtures thereof.

30. Use of the method according to any one of claims 16 to 26 for the production of a calibration band suitable for the production of a three-dimensional composite part by automated laying of said band by means of a robot.

31. 30. Use of a tape of impregnated fibre material according to any one of claims 27 to 29 in the manufacture of a three-dimensional composite part.

32. 32. Use according to claim 31, characterised in that the manufacture of the composite parts relates to the fields of transport, in particular automotive, oil and gas, in particular marine, gas storage, civil or military aviation, maritime, railways; renewable energy, in particular wind energy, tidal energy, energy storage devices, solar panels; insulation panels; sports and recreation, health and medicine, security and electronics.

33. Three-dimensional composite part, characterised in that it results from the use of at least one unidirectional band of impregnated fibre material according to any one of claims 27 to 29.